Kontribusi Komunikasi Politik Dalam Membangun Jejaring Koalisi Formulasi Kebijakan Minuman Keras Kota Surakarta - Yitno Puguh Martomo (Jurnal Ilmu Komunikasi PROGRESSIO, 2020)
The alcohol problem has a legal product at the top level on Presidential Regulation No. 74 of 2013, there are the control and supervision of alcohol. The regulatory authority or prohibition is given to the regional government. Therefore public policies in the form of regional regulations on liquor must be formulated in order to accommodate all interests.The method used is a qualitative descriptive approach, more emphasis on the expression of meaning and process of various factors under study, also intended to understand the phenomena about what is experienced by research subjects holistically.The formulation of policies regarding the handling of liquor in the city of Surakarta by using political communication in building a network model of an advocacy coalition was formed by actors who formed a coalition based on a system of values and beliefs that did not conflict. The strength of the core beliefs of each actor raises the conflict supported by a set of triggers, strengthening the development and position of the advocacy coalition. The actors in the policy advocacy coalition each work to formulate their own policies for the same goal of handling liquor in the city of Surakarta.